2010
DOI: 10.1007/s11060-010-0477-1
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal MRI evidence for decreased survival among periventricular glioblastoma

Abstract: While the prognosis of patients with glioblastoma (GBM) remains poor despite recent therapeutic advances, variable survival times suggest wide variation in tumor biology and an opportunity for stratified intervention. We used volumetric analysis and morphometrics to measure the spatial relationship between subventricular zone (SVZ) proximity and survival in a cohort of 39 newly diagnosed GBM patients. We collected T2-weighted and gadolinium-enhanced T1-weighted magnetic resonance images (MRI) at pre-operative,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
54
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(59 citation statements)
references
References 15 publications
4
54
1
Order By: Relevance
“…Repeated brain MRI scans are performed in many clinical scenarios, such as follow up of patients with tumors and therapy response assessment (Rees et al, 2009;Young et al, 2011;Weizman et al, 2012;Yip et al, 2014;Weizman et al, 2014). They constitute one of the most efficient tools to track pathology changes and to evaluate treatment efficacy in brain diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Repeated brain MRI scans are performed in many clinical scenarios, such as follow up of patients with tumors and therapy response assessment (Rees et al, 2009;Young et al, 2011;Weizman et al, 2012;Yip et al, 2014;Weizman et al, 2014). They constitute one of the most efficient tools to track pathology changes and to evaluate treatment efficacy in brain diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Recent clinical studies have suggested that lateral ventricle contact (LVC) of contrast-enhancing lesions (CELs) detected preoperatively by magnetic resonance imaging (MRI) are associated with poor survival in glioblastoma patients [4], and it was proposed that a more aggressive glioblastoma may originate from neural stem cells in the subventricular zone (SVZ) that have a propensity for invasion and proliferation [2,5,6]. In addition, LV-contacting and non-LV-contacting glioblastomas (LVCGs and NLVCGs, respectively) may have different cellular origins and compositions that could also have clinical implications.…”
Section: Introductionmentioning
confidence: 99%
“…However, previous studies did not examine molecular markers such as O 6 -methylguanine DNA methyltransferase (MGMT) promoter methylation [7] and isocitrate dehydrogenase (IDH) 1 mutation status [8,9] when evaluating the prognostic significance of LVC after standard therapy. Moreover, there is evidence that LVC may not reflect the point of origin of glioblastomas, and cannot be used to determine the cell of origin [10].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, those patients with SVZ involvement had an overall reduced survival as well as a decreased time until recurrence compared to those tumors not involving the SVZ. In addition, an analysis of 39 newly diagnosed GBM patients revealed that tumor SVZ involvement was a signifi cant predictor in reduced overall survival [ 38 ].…”
Section: Clinical and Therapeutic Implicationsmentioning
confidence: 99%